Feasibility of a Health‐Utility Approach to Quantifying Noneconomic Losses from Personal Injury. Issue 2 (6th April 2018) - Carvalho, Natalie; Fish, David; Grant, Genevieve M.; Salomon, Joshua A.; Studdert, David M.
Abstract : There is wide agreement that existing approaches to valuing noneconomic losses from personal injury lack coherence. "Health‐utility" measurement—an approach developed in health economics for valuing health outcomes in public health and medicine—holds considerable promise for bringing greater rationality and consistency to assessments of injury‐related noneconomic loss. However, the feasibility of creating utility measures that are suitable for use in personal injury compensation has not been demonstrated. This study takes that step. We surveyed more than 4, 100 members of the general public in Australia to assess people's preferences for a variety of nonfatal "health states." The health states were selected to reflect harms commonly seen in claims to compensation schemes for transport and workplace accidents. We then followed established methods for transforming the survey responses into a "severity weight" for each health state. We show how these severity weights can be used to define tiers in a schedule for guiding noneconomic damages determinations. We also discuss the strengths and limitations of the approach, and consider implementation challenges.